Kinetics of photocatalytic decomposition of Fenuron over TiO2 in aqueous solution - Ouarda Brahmia; Abdelaziz Boulkamh; Tahar Sehili; Jean-Pierre Aguer; Claire Richard (International Journal of Photoenergy)
The kinetics of the photocatalytic degradation of Fenuron (3-phenyl-1,1-dimethylurea) in aqueous suspension of several semiconductors irradiated at 365nm has been investigated. The kinetics of the reaction is well described by the Langmuir-Hinshelwood model showing that the degradation reactions occur on the semiconductors particles surface. The primary photoproducts were identified by RMN and GC/MS. The main initial reaction is hydroxylation in ortho and para position with respect to the urea function. The rate of the photocatalytic degradation increases upon addition of small amounts of hydrogen peroxide, but is slightly reduced by chloride ions.